Diagnostic Accuracy of the RIPASA Scoring System for Diagnosing Acute Appendicitis: A Study of 240 Patients - Attaullah Arif, Saifullah Brohi, Saira Mahmood, Zahid Saeed, Shamaila Ayub, Muhammad Faheem Anwer, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Acute appendicitis (AA) is a common surgical emergency, and accurate diagnosis is crucial to prevent complications such as perforation and peritonitis. The RIPASA scoring system, developed in India, is a clinical scoring tool that combines demographic, clinical, and laboratory parameters to assess the likelihood of acute appendicitis. This study aims to evaluate the diagnostic accuracy of the RIPASA score in diagnosing acute appendicitis in a cohort of 240 patients. Methods: A prospective observational study was conducted at Department of General Surgery Lady Reading Hospital Peshawar from August 2022 to July 2023, involving 240 patients who presented with suspected acute appendicitis. The RIPASA score was calculated for each patient based on clinical examination, symptoms, and laboratory findings. The final diagnosis of acute appendicitis was confirmed by histopathological examination. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy were calculated for the RIPASA score. Logistic regression analysis was performed to assess the relationship between the RIPASA score and the likelihood of acute appendicitis. Results: Out of 240 patients, 180 (75%) were diagnosed with acute appendicitis. The RIPASA score showed high diagnostic accuracy, with a sensitivity of 92.2%, specificity of 80.4%, PPV of 90.4%, NPV of 85.2%, and overall accuracy of 88.8%. The logistic regression model indicated that each point increase in the RIPASA score increased the odds of acute appendicitis by a factor of 1.35 (p < 0.001). The area under the curve (AUC) for the ROC analysis was 0.91, demonstrating excellent discriminatory power. Conclusion: The RIPASA scoring system is a highly sensitive and accurate tool for diagnosing acute appendicitis, particularly in resource-limited settings where imaging modalities may not be readily available. It provides an efficient, cost-effective alternative to more expensive diagnostic methods, and can significantly aid in clinical decision-making to prevent delays in diagnosis and treatment. Keywords: Acute Appendicitis, RIPASA Scoring System, Diagnostic Accuracy, Sensitivity and Specificity